2022
DOI: 10.1097/md.0000000000032444
|View full text |Cite
|
Sign up to set email alerts
|

A pan-cancer analysis of the oncogenic role of procollagen C-endopeptidase enhancer (PCOLCE) in human

Abstract: There is no evidence showing that the expression of procollagen C-endopeptidase enhancer (PCOLCE) is associated with human tumors, and pan-cancer analysis is not available. Based on public databases such as the cancer genome atlas, we investigated the potential role of PCOLCE expression in 33 different human tumors. PCOLCE expression in 11 tumors was significantly correlated with tumor prognosis and was a prognostic predictor for pancreatic adenocarcinoma, thymoma and CES. We also found that PCOLCE expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Previous studies have suggested that PCOLCE-AS1 is downregulated in gastric cancer and acts as a tumor suppressor by regulating the expression of PCOLCE, which encodes an enzyme that enhances the activity of procollagen C-endopeptidase of procollagen types I-III [ 45 ]. Additionally, PCOLCE-AS1 may also modulate the immune infiltration and response of various immune cells, such as B cells, T cells, macrophages, neutrophils, and dendritic cells, in gastric cancer [ 46 ]. In this study, we found that the expression of PCOLCE-AS1 was positively correlated with periodontitis and significantly positively associated with plasma cell infiltration and the activation of most immune pathways, particularly the interferon receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have suggested that PCOLCE-AS1 is downregulated in gastric cancer and acts as a tumor suppressor by regulating the expression of PCOLCE, which encodes an enzyme that enhances the activity of procollagen C-endopeptidase of procollagen types I-III [ 45 ]. Additionally, PCOLCE-AS1 may also modulate the immune infiltration and response of various immune cells, such as B cells, T cells, macrophages, neutrophils, and dendritic cells, in gastric cancer [ 46 ]. In this study, we found that the expression of PCOLCE-AS1 was positively correlated with periodontitis and significantly positively associated with plasma cell infiltration and the activation of most immune pathways, particularly the interferon receptor pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Another enzyme driving collagen rearrangements and recently associated with immune infiltrating cells is PCOLCE, which localizes in the TME of several cancer types. Bioinformatic analyses highlighted that PCOLCE is a prognostic predictor for PAAD, thymoma and CES ( 51 ). Even if the molecular mechanisms behind this observation are still unknown, PCOLCE expression correlates with the extent of CD4 + T, CD8 + T, NK cell infiltration.…”
Section: Resultsmentioning
confidence: 99%
“…Dysregulation of this mechanism can lead to carcinogenesis and has been documented to be related to increased PCOLCE levels in multiple cancers. According to an analysis of The Cancer Genome Atlas, increased expression of PCOLCE can confer poor prognosis in esophageal cancers, although the frequency in which PCOLCE becomes dysregulated is relatively low [ 56 ]. Additionally, The Cancer Genome Atlas groups all types of esophageal cancers together, making its exact relationship to EAC difficult to identify.…”
Section: Discussionmentioning
confidence: 99%